Description of Sleep in Cancer Patients Undergoing Chemotherapy - Kustriyani, Menik (South East Asia Nursing Research, 2023)
Sleep disturbances are prevalent among cancer patients undergoing chemotherapy, significantly impacting their quality of life and potentially influencing treatment outcomes. This systematic review explores the characteristics, prevalence, and contributing factors to sleep disturbances in this population, alongside an evaluation of potential interventions. The findings emphasize the need for comprehensive management strategies that address both the physiological and psychological aspects of sleep disturbances. A combination of pharmacological and non-pharmacological treatments, tailored to individual patient needs, emerges as the most effective approach to improve sleep quality in these patients.